SUCCESSFUL TREATMENT OF CLASS III DENTOSKELETAL MALOCCLUSION WITH LOWER MOLAR EXTRACTION - Valencia Ignes Tan; Zenith Paskalin; Avi Laviana; Ida Ayu Evangelina; Elih Sayuti; Endah Mardiati (FKG ULM, 2025)
Background: Class III dentoskeletal malocclusion presents a significant clinical challenge, particularly in adult patients, due to limited skeletal growth potential and complex occlusal discrepancies. Non-surgical management often relies on dental compensation strategies, including selective extractions and transverse expansion to achieve functional and aesthetic outcomes. Objectives: This report aims to demonstrate the successful management of a mild skeletal Class III malocclusion using first mandibular molar extractions and maxillary expansion via quad helix appliance, as an alternative to orthognathic surgery. Case: A 20-year-old female patient presented with ectopic canines, chewing difficulty, and facial aesthetic concerns. Clinical and radiographic evaluations revealed a skeletal Class III relationship, bilateral anterior and posterior crossbites, and crowding. Notably, the patient had large composite restorations and overfilled endodontic treatments on her lower first molars. Case Management: A non-surgical orthodontic treatment was planned and executed. This included bilateral extraction of the first lower molars, maxillary expansion using a quad helix appliance, and fixed appliance therapy with a Roth-prescription straight-wire system. The treatment was followed by midline correction, retraction, and use of Class III elastics to achieve Class I molar and canine relationships. The retention phase involved clear retainers for both arches. Conclusion: The combination of lower first molar extraction and quad helix expansion provided an effective camouflage for a mild skeletal Class III malocclusion, improving facial aesthetics, correcting crossbites, and achieving stable functional occlusion. This case supports the viability of non-surgical orthodontic compensation in carefully selected adult Class III patients. Keywords: class III dentoskeletal malocclusion, first lower molar extraction, quad helix